The Effect of Out Class Learning Design on Students' Creative Thinking Ability in Social Studies Learning for Grade IV Elementary School Students - Siti Dewi Maharani; Azizah Husin; Marwan Pulungan (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractThis study aims to determine the effect of learning design outside the classroom on students' creative thinking skills in social studies learning for fourth-grade elementary school students. This research uses an experimental research method with a quasi-experimental research design non-equivalent control group design. The population of this research is the fourth-grade students of one of the elementary school in Palembang. The samples obtained are the control class in class IVc which consists of 35 students, and the experimental class in class IVa, which consists of 33 students. Data was taken using pretest-posttest and then tested with normality and homogeneity tests. Then given treatment and tested the hypothesis using the independent sample t-test. From the test results, it was found that in testing the dependent variable, the results obtained sig. <0.05, with a score of 0.007 and the result is lower than the significance value. The results of the test state that Ho is rejected and Ha is accepted, which means that there is a difference in influence between the experimental class and the control class in creative thinking skills. So, the design of outclass learning is more effective than direct learning in improving students' creative thinking skills in social studies learning.Keywords: creative thinking, elementary school students, outclass learning.Â AbstrakPenelitian ini bertujuan untuk menentukan pengaruh desain pembelajaran di luar kelas terhadap kemampuan berpikir kreatif siswa pada pembelajaran IPS siswa kelas IV Sekolah Dasar. Penelitian ini menggunakan metode penelitian eksperimen dengan desain penelitian quasi eksperimen non-equivalent control group design. Populasi penelitian ini adalah siswa kelas IV salah satu sekolah dasar di Palembang, Indonesia dan sampel yang diperoleh adalah kelas kontrol di kelas IVc yang berjumlah 35 siswa dan kelas eksperimen di kelas IVa yang berjumlah 33 siswa. Data diambil dengan memberikan pretest-posttest kemudian diuji dengan uji normalitas dan uji homogenitas. Kemudian diberikan perlakuan dan diuji hipotesis dengan menggunakan independent sample t-test. Dari hasil pengujian diketahui bahwa pada pengujian variabel dependen diperoleh hasil sig. < 0,05, dengan skor 0,007 dan hasilnya lebih rendah dari nilai signifikansinya. Hasil pengujian menyatakan Ho ditolak dan Ha diterima yang berarti terdapat perbedaan pengaruh antara kelas eksperimen dan kelas kontrol terhadap keterampilan berpikir kreatif siswa. Sehingga dapat disimpulkan bahwa desain pembelajaran di luar kelas lebih efektif dari pada pembelajaran langsung dalam meningkatkan kemampuan berpikir kreatif siswa pada pembelajaran IPS.Kata kunci: berpikir kreatif, siswa sekolah dasar, pembelajaran di luar kelas.